PENGARUH KEPEMIMPINAN, KOMITMEN ORGANISASI, MOTIVASI DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR PELAYANAN PAJAK PRATAMA MEDAN TIMUR - Erikson Sinaga; Deliana Magdalena Hutajulu; Hendra Amin Syahputra; Ike Ristianti; Bobby Muhar (Universitas Islam Islam Sumatera Utara, 2021)
The problems in this research are: How is the influence of leadership, organizational commitment, motivation and job satisfaction partially and simultaneously on the performance of employees at the Pratama Tax Office in East Medan? Research objectives: To determine the effect of leadership, organizational commitment, motivation and job satisfaction partially and simultaneously on employee performance at the Pratama Tax Office, East Medan. The proposed hypothesis is: There is a significant influence of leadership, organizational commitment, motivation and job satisfaction partially and jointly on the performance of employees at the Pratama Tax Office, East Medan. The study was conducted at the Pratama Medan Timur Tax Service Office, Jalan Sukamulia Number 17A, Medan City, North Sumatra Province, zip code 20152, with a population of 113 people, and the research sample as many as 90 people. Sources of data used are primary data obtained from the distribution of questionnaires, interviews and documentation that was tested with IBM Statistics 24.00 for windows. Based on the analysis results obtained leadership have a positive and significant effect on the performance of employees work of the Kantor Pelayanan Pajak Pratama Medan Timur, this is supported by the results of t count analysis t-table (5,041 1,988) at n = 90 at 95% significance level. Organizational commitment has a positif and significant effect on the performance of employees work of the Primary Tax Service Office of Medan Timur, this is supported by an analysis of t count t-table (2,617 1,988) at n = 90 at 95% significance level. Motivation has a not effect on the performance of employees work of the Kantor Pelayanan Pajak Pratama Medan Timur, this is supported by an analysis of t count -table (0,542 1,988) at n = 90 with a significant level of 95%. Job satisfaction has a effect on the performance of employees work of the Kantor Pelayanan Pajak Pratama Medan Timur, this is supported by an analysis of t count -table (2,282 1,988) at n = 90 with a significant level of 95%. Value of F-count F table (12,615 2,48) This states that together (multiple) there are positive and significant effects of leadership, organizational commitment and motivation on the performance of employees work of employees of the Kantor Pelayanan Pajak Pratama Medan Timur . Thus the hypothesis proposed is accepted by the truth Â